Pengembangan panduan model konseling solution facused brief counseling teknik imagery and visualitation berbasis website SI- konseling untuk mengatasi depresi pada remaja korban kekerasan - Fitri, Inda Ramadani; Suranata, Kadek; Arwati, Kadek Ari Dwi (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
The purpose of this research is to develop and test the adequacy and effectiveness of the guideline content. counseling model solution focused brief counseling imagery and visualitation techniques based on the SI-Counseling website to overcome depression in adolescent victims of violence. Such studies are included in development studies using the 4D methodology (Define, Design, Develop, Disseminate). Two counseling instructors participated in this study as well as 1 educational technology lecturer as an expert and 1 counseling teacher at SMK Negeri 2 Singaraja and 1 counselor from the Office of Population Control, Family Planning, Women's Empowerment and Child Protection in Buleleng Regency as practitioners tasked with testing the usability, correctness, and enforceability of policies. From the assessment carried out, it proves that the solution focused counseling model guide book, imagery and visualitation technique brief counseling, meets the terms and conditions for use. The ES value in counseling is included in the high category, namely ES: 1.66.